Microstructure and Properties of Ti80 Alloy Fabricated by Hydrogen-Assisted Blended Elemental Powder Metallurgy - Wang, Baicheng; Lei, Peng; Ma, Guangyu; Li, Dongdong; Savvakin, Dmytro; Ivasishin, Orest (Frontiers in Materials, 2020)
Ti80 (Ti-6Al-3Nb-2Zr-1Mo) is a recently developed near-α titanium alloy that is generally applied in marine applications. In this study, the feasibility of producing the Ti80 alloy via the blended elemental powder metallurgy (BEPM) press-and-sinter method was demonstrated. Generally, the presence of elements with low diffusion mobility in titanium (Mo, Nb) creates difficulties with diffusion-controlled healing of the porosity and the realization of microstructural uniformity. These issues were minimized by using titanium hydride powder instead of titanium powder to activate the sintering, as well as by the proper selection of complex alloying powders rather than elemental powders to promote alloy uniformity. The time-temperature conditions to obtain a chemically and microstructurally homogeneous and nearly-dense alloy microstructure were determined. Special attention was given to the microstructural peculiarities of the sintered material to regulate its mechanical characteristics. Finally, the processing parameters were determined to reach the properties required by alloy specifications. This enabled both the fully beta transformed lamellar microstructure inherent to beta phase field sintering and one that could be modified via post sintering thermomechanical processing.